Identifying the main drivers of the spatiotemporal variations in wetland methane emissions during 2001–2020 - Hu, Yihan; Yue, Xu; Tian, Chenguang; Zhou, Hao; Fu, Weijie; Zhao, Xu; Zhao, Yuan; Chen, Yuwen (Frontiers in Environmental Science, 2023)
Wetlands act as an important natural source of global methane (CH4). The emission rate of wetland CH4 is jointly affected by climate change, carbon dioxide (CO2) fertilization, and wetland distribution. In this study, we implemented a wetland CH4 emission module into the Yale Interactive Biosphere (YIBs) model to quantify the spatiotemporal variations of global wetland CH4 emissions in 2001-2020. Site-level validations showed that the YIBs model reasonably captures the seasonality and magnitude of CH4 emissions at 28 out of 33 sites with significantly positive correlations and low relative biases. On the global scale, the YIBs predicts an annual mean wetland CH4 emission of 147.5 Tg yr -1 in 2000-2017, very close to the estimate of 147.9 Tg yr - 1 from the ensemble of 13 process-based models. Global wetland CH4 emissions showed a positive trend of 0.74 Tg yr -2 in the past two decades, leading to an increase of 7.4 Tg yr -1 (5.2%) in 2008-2017 than 2000-2009. Climate change and CO2fertilization accounted for over 70% of global wetland CH4 emission changes. Among them, the impact of CO2 grew steadily and became the dominant factor after the year 2008. The most significant changes in wetland CH4 emissions were located in the tropical regions following the perturbations in temperature that drives the ecosystem productivity. We found limited changes in CH4 emissions over high latitudes because of the moderate variations in wetland area fraction. The rise of wetland CH4 emissions poses an emerging threat to the global warming and likely escalates the tropospheric air pollutants.